2020
DOI: 10.52547/jccs.1.3.121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Intelligence Training on Hope in Patients with Chronic Kidney Disease Undergoing Hemodialysis: A Randomized Clinical Trial Study

Abstract: Perception of illness in patients undergoing ... [2] Comparison between anxiety, depression ... [3] The relationship between self-esteem and ... [4] Prevalence of chronic kidney disease in population ... [5] The multidimensional characteristics of symptoms ... [6] Iranian year view of dialysis in ... [7] Sleep quality and spiritual well-being in hemodialysis ... [8] Reasons of chronic renal failure in hemodialysis patients ... [9] Frequency of mental disturbances in hemodialysis patients ... [10] The relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Practicing religious beliefs and practices in the context of spirituality and/or religiosity as coping mechanisms, especially as a source of calm, peace, comfort, strength, and support, can help improve hope, mental health, and quality of life for patients (Abu et al, 2018;Bravin et al, 2019;Santos et al, 2017;Tavassoli et al, 2019). Religious services, including spiritual (Yuliani et al) intelligence training, can be done to serve the spiritual needs of hemodialysis patients (Hosseinpour et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Practicing religious beliefs and practices in the context of spirituality and/or religiosity as coping mechanisms, especially as a source of calm, peace, comfort, strength, and support, can help improve hope, mental health, and quality of life for patients (Abu et al, 2018;Bravin et al, 2019;Santos et al, 2017;Tavassoli et al, 2019). Religious services, including spiritual (Yuliani et al) intelligence training, can be done to serve the spiritual needs of hemodialysis patients (Hosseinpour et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare, some researchers, most of them in Iran, have tried to develop SI as way to help people cope with existential challenges. For example, two independent studies (Hosseinpour et al 2020;Pasyar et al 2020) showed that training in Spiritual Intelligence and subsequent assessment using Amram and Dryer's (2008) ISIS and King's SISRI-24 (King and DeCicco 2009), respectively, have a positive effect on hope and life expectancy among the chronically ill. Others have trained care providers in SI to work with patients. Riahi et al (2018) found that SI training improved nurses' competence in spiritual care in critical care units, which in turn improved patient quality of life.…”
Section: Developing Spiritual Intelligencementioning
confidence: 99%
“…Furthermore, although some SI scales have been developed to be culturally specific (e.g., Dhar and Dhar 2010;Jumahat et al 2015;Kumar and Mehta 2011), others (e.g., Amram and Dryer 2008;King and DeCicco 2009) have demonstrated cross-cultural validity. SI, while an innate capacity, is one that, like any other intelligence, can be cultivated (e.g., Charkhabi et al 2014;Heydari et al 2017Heydari et al , 2018Hosseinpour et al 2020). Importantly, as an intelligence, SI has been shown in numerous studies to be associated with and to predict various positive outcomes cross-culturally (e.g., Amirian and Fazilat-Pour 2016;Khosravi and Nikmanesh 2014;Kaur et al 2015;Mansouri et al 2016;Pant and Srivastava 2019;Pasyar et al 2020).…”
Section: Introductionmentioning
confidence: 99%